Implementation of TQM in public universities of Bangladesh: challenges and resolutions: a review - Hossin, M.M Ismail; Islam, Mohd Aminul; Uddin, Mohi (Scholars Middle East Publishers, 2018)
Education intends to promote such values and improve people’s capacity that sustains environment and development issues of any countries. Education helps to create awareness, welfare attitudes, skills and behaviour as well as a sense of ethical responsibilities among the people. Education has different levels such as primary, secondary, higher secondary and university education. Among these, university or higher education is one of the fastest growing parts of the education system. In these contexts, higher education should be standard, welfare and sustainable development oriented. One of the key aims of higher education is to anticipate the needs of the economy and prepare highly skilled workers to make it competitive. This is especially important for a developing country like Bangladesh. Because, it is badly needed to build up our human capital, and higher education can play vital role in this regard that promotes to the growth of economy, achieve and sustain a high-quality workforce. But higher education is now globalized and in many ways commercialized affair. As a result, quality of higher education is ignored, and business attitude prioritized, especially in the context of third world countries. As a developing country, in Bangladesh, this scenario is more vulnerable.